Konsep diri remaja Kristen dalam menghadapi identitiy crisis sosial media - Abraham, Victor; Paulus, Yanto (Davar : Jurnal Teologi, 2023)
ABSTRACTAs children of God, youth are endowed with the seeds of Christ's character within. Therefore, in order to grow and maintain the character of Christ in him, he must understand his identity as a follower of Christ. Therefore, Christian youth must provide a real foundation where they will not be influenced by the surrounding influences, especially the influence that is on social media. So that when they enter a period of identity crisis, Christian youth are ready to take their journey to find their identity. The existence of this journal aims to reduce Christian teenagers who experience "identity crisis" due to their environment, especially in social media. Also so that people who want to help their friends or teenagers to be able to go through the ups and downs of youth with a self-concept and self-identity in accordance with the Christian Faith. The benefits obtained from the journal are a guidebook that can help them through their teenage years so that Christian Teens or children who are heading to Teenagers and parents who have Teenagers for them can understand and anticipate things that will happen to them and build certainly a strong foundation of the Christian Faith in order to be able to go through that period without experiencing an "identity crisis". Key words: Identity, Social media, Identity crisis, Christian youth, Self concept. ABSTRAKSebagai anak Tuhan, pemuda diberkahi dengan benih karakter Kristus dalam diri. Oleh karena itu, untuk mendapatkan tumbuh dan pertahankan karakter Kristus di dalam dirinya, maka dia harus memahami identitasnya sebagai pengikut Kristus. Maka dari itu para remaja Kristen harus dibekali betul-betul fondasi dimana mereka tidak akan terkecohkan oleh pengaruh sekitar terutama pengaruh yang ada pada sosial media. Sehingga pada saat mereka memasuki periode krisis identitas, para remaja Kristen sudah siap untuk menempuh perjalanan mereka untuk mencari identitas sejati dirinya. Adanya jurnal ini bertujuan agar mengurangi Remaja Kristen yang mengalami identity crisis” akibat lingkungan mereka terutama dalam sosial media. Juga agar para orang yang ingin membantu teman atau anak remaja mereka untuk dapat melewati masa-masa naik turunnya keremajaan dengan konsep diri dan identitas diri yang sesuai dengan Iman Kristen. Manfaat yang didapat dari jurnal yaitu sebuah buku panduan yang dapat membantu mereka melalui masa remaja mereke agar para Remaja Kristen atau anak yang sedang menuju ke Remaja serta orang tua yang memiliki anak Remaja untuk mereka dapat memahami dan mengantisipasi terhadap hal-hal yang akan menimpa mereka dan tentunya membangun sebuah fondasi Iman Kristen yang kuat agar bisa melalui masa itu tanpa mengalami “identity crisis”. Kata kunci: Identitas, Sosial media, Krisis identitas, Remaja Kristen, Konsep diri.